Fatores associados ao declínio cognitivo em idosos com hipertensão: uma revisão sistemática - Cabral, Sátila Adriely Moreira (2025)
INTRODUCTION: Aging causes a physiological decline in bodily and neurobiological functions, increasing vulnerability and susceptibility to chronic noncommunicable diseases. Systemic Arterial Hypertension (SAH) and cognitive decline are interconnected conditions, and their combined investigation is crucial. SAH, especially at younger ages, accelerates cognitive decline by causing microvascular damage in the brain. Controlling hypertension can mitigate these effects. Therefore, combined investigation is justified by the need for an integrated approach that prevents the progression of both conditions and preserves long-term brain health. OBJECTIVE: To identify the factors associated with cognitive decline in older adults diagnosed with hypertension through a systematic review. METHOD: This is a systematic literature review guided by the recommendations of The Joanna Briggs Institute. The research question was formulated based on the PEO strategy, in which "P" represents the population (elderly individuals), "E" the exposure (hypertension), and "O" the outcome (cognitive decline). The following databases were used for the search: National Center for Biotechnology Information (NCBI)/PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Excerpta Médica Database (EMBASE). RESULTS: Fourteen articles were selected for this study, following the eligibility criteria. The studies analyzed presented methodological and population diversity. The study samples included older adults predominantly between 70 and 75 years old, from different geographic contexts. Notably, 50% (n=7) of the studies included samples from China. The main factors associated with cognitive decline were hypertension, blood pressure control, cognitive frailty, comorbidities, and progression to dementia. CONCLUSION: The findings highlight the importance of increasing awareness of early detection of cognitive decline, as this favors more effective interventions and contributes to the implementation of strategies that improve quality of life in older adults.